Emprego de plasma rico em plaquetas associado à esponja cirúrgica em enxertos cutâneos em coelhos (Oryctolagus cuniculus) - Pazzini, Josiane Morais [UNESP]; Serafim, Eduardo Luis [UNESP]; Uscategui, Ricardo Ramirez Andrez [UNESP]; De Almeida, Vivian Tavares [UNESP]; Oliva, Carlos Alfredo Calpaa [UNESP]; Gärtner, Fátima; De Carvalho, Maria De Fátima Faria; De Paula Reis, Nazilton [UNESP]; Ferreira, Marília Gabriele Prado Albuquerque [UNESP]; Moraes, Paola Castro [UNESP]; De Oliveira, João Ademir [UNESP]; De Nardi, Andrigo Barboza [UNESP] (My University, 2016)
This work had the purpose to evaluate the effectiveness of PRP gel use associated with surgical sponges improve the integration of skin graft to receptor site. Was conducted a study of 16 rabbits, New Zealand white, female, 60 days old. They were divided into two groups with eight animals each, all of which was undergoing reconstructive surgery technique for making mesh graft. The groups were constituted in Gprpme received PRP gel and Gcme who received 0.9% saline solution combining both surgical sponge as a way of curative. The blood samples the Gprpme group that was done PRP, the mean platelet count after centrifugation was 1,288,750 platelets/uL. The results obtained in the PRP final sample when compared to the inicial were significantly greater. Thus, the double centrifugation protocol for obtaining PRP which was performed in this trial was appropriate, because the platelet concentration after double centrifugation increased three times as compared with the initial count of the blood sample, and it was possible to achieve good therapeutic results. In the macroscopic evaluation of the 3rd day, exudate showed significant differences in Gprpme compared to Gcme. In the evaluations of the 7th and the 14th day edema, flushing, color, exudate and cosmetic appearance were not significant between the groups. Qualitative histological evaluations using the staining HE and Trichromes of Massom, it was observed that the intensity of polymorphonuclear cells, fibroblast proliferation, collagen deposition and epithelialization no significant difference. However, the vascular proliferation was significantly higher in the Gprpme when comparison with the Gcme. Therefore, the use of platelet rich plasma in the form of gel using in meshed skin grafts are able to stimulate angiogenesis in wound, favoring integration of the graft to site receptor, without the presence of granulation tissue. And association of surgical sponge as a pressure dressing promotes healing of the graft, reducing complications such as presence of edema, and graft movement, therefore is feasible and advisable his use.
Rich plasma platelets employed with surgical sponge in skin grafts in rabbits (Oryctolagus cuniculus)
Keywords: Compressive curative; Graft; Neovascularization; PRP; Rabbits; Wounds